Novel Treatments for Alzheimer’s Disease - Hashemi, Mansoureh; Zali, Alireza (International Clinical Neuroscience Journal, 2017)
Alzheimer’s disease (AD) is a multifarious neurodegenerative disorder that leads to cognitive impairment and dementia in late adult life. Pathology hallmarks of Alzheimer’s disease were observed intracellular neurofibrillary tangles and extracellular amyloidal protein. According to pathology of this disease, abundant studies were performed with focused on pharmacological therapeutics over the last two decades. Current treatments for AD are acetylcholinesterase inhibitors (rivastigmine, galantamine, donepezil) and N-methyl D-aspartate receptor antagonist (memantine) that can decrease the progression of the disease. In this review, authors will discuss the various aspects of pathophysiological mechanisms and therapeutic strategies of Alzheimer’s disease.